The main demographic characteristics of customers and the frequency of purchases organic food - Mitić, Vladimir; Čolović, Milica (Ekonomika poljoprivrede (1979), 2022)
The essential research goal is to determine the frequency of purchases organic food in general and the basic demographic characteristics of typical buyers of organic food. Sample consists of 571 respondents of different sex, age, and educational level, area of living, material and marital status. The research was conducted online using a Google. The SPSS program was used for data processing. The Man Witney U and the Kruskal - Wallis tests were applied in order to determine the statistical significance of the obtained differences in scores between groups of subjects. The obtained results showed that the frequency of purchasing organic food in Serbia is still low. Typical buyers of organic food are mostly women, older, have higher education and income. They usually live in urban areas, in big cities, while their marital status seems to have no influence on their decision to purchase an organic food and products.